Zoró : Aldeia Escola Zarup Wej : ensino médio, currículo e ensino de história (1989-2013) - Santos, Devanir Aparecido dos (2014)
This study gives an insight into the attempts of the state to respond to the problems faced by indigenous communities in the field of school‟s education. It is shown as an overview of the regulatory development to provide a specific academic education for Brazils indigenous people. Analyzes, concisely, the challenges for ensuring this kind of education, and advances more specifically, in a way to understand the implementation process of education for Zoro. It also shows the conditioning factors and expectations of these people by the new education model, besides its participation in the educational process. The development of the educational process for Zoro required the construction of small schools in villages, after, with increasing needs to have further studies, were built schools-villages, for primary education, and later, for high school. Its structural implementation tried, under the physical point of view, get close to the maximum of the students cultural reality in order to bring the children to the school and to avoid school‟s dropout and grade repetition. Try to present the organization of the curriculum grade and is used, as a sample, the subject of History to understand how is articulated shortages and production of specific instructional materials for teaching the Zoro students. Added to this, the attempt to understand the pedagogical practice in Zoro school, from the history teaching, and the working system of the students achievement and evaluation. Concludes by presenting how efficiently the laws are in the local reality of the school-village in Zarup Wej.